Power and Branding: Language Commodification of Tourist Resorts - Asrofin Nur Kholifah; Ika Maratus Sholikhah; Erna Wardani (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
Exploitation of language in commercial sector is inexorable. Language does not only work to articulate meaning but also to send and build image. In this sense, language has been commodified. This fact becomes more obvious in tourism industry in which language plays vital role to construct brand as well as to reach targeted profit. Based on these premises, this research aims to unravel the phenomenon of language commodification in Baturraden Tourism areas within the framework of Linguistic Landscape. The descriptive qualitative research was conducted through observation, documentation and interview. Data in the forms of photographs were gathered to be analyzed and interpreted to capture the language commodification manifested in the selected areas. The analysis shows that language commodification is materialized through the use of Indonesian, English and Javanese. English serves a dominant language in this tourism industry. Most tourist destinations prefer using English to Indonesian as national language to label their place. The issue of branding therefore becomes obvious to elevate the market and effectively attract the visitors. English, rather than functions as referential meaning, serves economic functions. Here, English is more powerful than other given languages. English offers higher prestige, modernity and promising brand to be beneficial for this industry. Then, Javanese is maintained to introduce the history or local legend as well as to bring the sense of authenticity.